Жан Анрі Фабр – великий натураліст і ентомолог - Кrut’, M. V. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2018)
During 30 years Jean-Anri Fabre had been studying insects and retained a greatest literary legacy. His dissertation was devoted to digger wasps (Sphecidae), with emphasis on their food specialization and habits. At the field entomological station Fabre studied development and mode of life of beetles (Attelabidae, Scarabaeidae, Silphidae), flies, other insects and scorpions. He detected the phenomenon of hypermetamorphosis in development of beetle Sitaris muralis (Meloidae), revealed the extra-intestinal digestion of fly larvae, drawn a conclusion about existence of insects’ instinct. The results of research works were published in 10 volumes of book entitled «Entomological Memoirs», among these four books were devoted to wasps. Other books of Fabre are «The Life of Insects», «Instinct and Customs of Insects», «Dung Beetles», «Wasps», «Bees». Fabre’s ideas are of importance for agriculture and forestry. His observations revealed new possibilities of insect pests’ control. It is possible to draw data on biological method of control from his exact descriptions. Jean-Anri Fabre was chosen an honorary member of Russian entomological society.